Eight-Channel LAN WDM (De)Multiplexer Based on Cascaded Mach–Zehnder Interferometer on SOI for 400GbE - Zhizun Zhao; Zhen Li; Jiaqi Niu; Gaolu Zhang; Hongliang Chen; Xin Fu; Lin Yang (Photonics, 2022)
In this paper, we design and experimentally demonstrate an eight-channel cascaded Mach–Zehnder interferometer (MZI) based Local Area Network (LAN) Wavelength Division Multiplexing (WDM) (de)multiplexerwith channel spacing of 800 GHz on a silicon-on-insulator. By cascading a three-stage MZI, eight target wavelengths are (de)multiplexed. The length difference of the third-stage MZI delay arms is adjusted so that the output channels skip the guard band. In order to keep the central wavelength of each channel from shifting, we utilize a wide waveguide for the phase delay arm in MZI to achieve large fabrication tolerance, and the multi-mode interference (MMI) couplers as power splitters with weak dispersions. The measurement results of the fabricated device show the precise wavelength alignment over the whole working wavelength range.